Access to finance and women entrepreneurship development in the Kigezi subregion, Uganda - Eton, Marus; Dianah, Nkamusiima (Routledge Taylor & Francis group, 2022)
Women entrepreneurs are challenged by access to finance in their quest to start any entrepreneurial activity. Global business failures have not spared women entrepreneurs; hence, this study is very significant, as it may direct the path to new business venture creation by women entrepreneurs. The provision of financial support to a business enterprise does not guarantee its success or growth. The study explored the role access to finance plays in entrepreneurship development, the strategies that stimulate women’s entrepreneurship, and the relationship between access to finance and entrepreneurship development. We used beta coefficients to quantify the effects of access to finance on entrepreneurship development. The findings revealed that women entrepreneurs find it difficult to access cheap and adequate financial services. The study recommends increased funding, development of good policies, and entrepreneurship training and education for women-owned businesses in order to strengthen women’s entrepreneurship development.